Evaluation of the Diagnostic Potential of a Plasma Exosomal miRNAs Panel for Gastric Cancer - Yang, Jiajia; Li, Xuan; Wei, Shuchun; Peng, Lei; Sang, Huaiming; Jin, Duochen; Chen, Meihong; Dang, Yini; Zhang, Guoxin (Frontiers in Oncology, 2021)
Purpose Gastric cancer (GC) is often difficult to diagnose early in the disease and remains one of the most frequently occurring malignancies. This investigation looks at the diagnostic potential of a specific plasma exosomal miRNAs panel for GC. Methods This study analysed 216 individual peripheral blood samples. 2 GEO datasets were analysed and two miRNAs were selected - plasma exosomal miR-195-5p and miR-211-5p. Quantitative reverse-transcriptase PCR (qRT–PCR) was used to assess relative expressions and receiver operating characteristic (ROC) curve analysis was used to determine the diagnostic efficiency of miR-195-5p and miR-211-5p panel. The Kaplan-Meier method was used to assess the prognostic value of plasma exosomal miR-195-5p and miR-211-5p. Results GC patients possessed notably raised plasma levels of exosomal miR-195-5p and miR-211-5p. The area under ROC curves (AUCs) of miR-195-5p , miR-211-5p were 0.745 , 0.798 in the screening phase and 0.762, 0.798 in the training stage respectively. GC was able to be diagnosed more accurately when both miRNAs were interpreted together (AUC=0.820 in the validation stage). Poorer prognosis was observed in GC patients who had plasma exosomal miR-195-5p and miR-211-5p of higher levels. In vitro experiments also confirmed that miR-195-5p and miR-211-5p is able to be transmitted between cells, and works to enhance tumor invasion, migration and proliferation while inhibiting cell apoptosis. Conclusion Plasma exosomal miR-195-5p and miR-211-5p may become potential biomarkers for GC diagnosis, and may be useful in predicting tumor phenotype.